Marine site polymer concrete capable of resisting steel bar corrosion and preparation method thereof

By adding specific components to the polyconcrete of the sea site, improving the structure and protection of steel bars, the problem of inability to fundamentally prevent corrosion of marine concrete and steel bars in the prior art is solved, and higher durability and corrosion resistance are achieved.

CN119551935AInactive Publication Date: 2025-03-04ZHEJIANG UNIV

Patent Information

Application Number
CN202411482559.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art can only slow down the corrosion of marine concrete and internal steel bars from the surface, and cannot fundamentally prevent corrosion, especially after the external anti-corrosion layer is damaged.

Method used

A kind of sea construction site polymer concrete that resists steel bar corrosion is used, and its components include coarse aggregates, fine aggregates, gel materials, calcium nitrite, sodium carbonate, sodium sulfate, alcohol amine compounds, zeolite molecular sieve, nano-scale silica powder and admixtures. Through the combination of these components, the pore structure of the concrete and the protection of steel bars are improved.

Benefits of technology

It effectively improves the durability and corrosion resistance of polymer concrete on marine construction sites, and ensures the safety and long-term stability of marine reinforced concrete structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097812200000081
    Figure BDA0005097812200000081
  • Figure BDA0005097812200000091
    Figure BDA0005097812200000091
Patent Text Reader

Abstract

The invention provides a reinforcing steel bar corrosion resistant marine site polymer concrete and a preparation method thereof, and relates to the technical field of building concrete preparation. The reinforcing steel bar corrosion resistant marine site polymer concrete is prepared from the following components in percentage by mass: 20 to 30 percent of coarse aggregate, 10 to 20 percent of calcium nitrite, 3 to 5 percent of sodium carbonate, 3 to 5 percent of sodium sulfate, 0.6 to 1.0 percent of alcohol amine compound, 5 to 10 percent of zeolite molecular sieve, 3 to 5 percent of nanoscale silicon dioxide powder, 1 to 5 percent of additive and the balance of water. According to the invention, the coarse aggregate is added into the raw materials, the calcined hydrotalcite is small in particle size and large in specific surface area, and can be used as a seed crystal to accelerate the hydration process in the early stage, so that more hydration products and a more compact structure are generated, and meanwhile, the calcined hydrotalcite can be filled in pores of a matrix to improve the pore structure, a slurry-aggregate interface and the like; chloride ions and CO2 are prevented from entering the matrix, and the durability of the sea site polymer and the concrete thereof is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building concrete preparation, in particular to a marine geopolymer concrete resistant to steel bar corrosion and a preparation method thereof. Background Art

[0002] In marine engineering construction, the durability and corrosion resistance of concrete used in marine construction projects are particularly important because seawater is rich in chloride ions and sulfates, which are extremely corrosive to concrete. The main reasons are:

[0003] First, factors of concrete itself: alkaline substances in concrete react with acidic substances, causing the pH value of concrete pore solution to decrease, thereby reducing the alkalinity of concrete and causing the steel bars to lose the protection of the passivation layer;

[0004] Second, the chloride ions carried by concrete itself and rich in seawater have a small radius and strong penetrating ability. They are strong depassivating agents. Chloride ions are adsorbed on the local passivation film, which rapidly reduces the pH value there, thereby destroying the passivation film on the surface of the steel bar and accelerating the corrosion of the steel bar.

[0005] Third, due to the infiltration of seawater, the magnesium salts and sulfates in the seawater react with the calcium hydroxide in the cement stone to form magnesium hydroxide, ettringite, magnesium silicate hydrate, calcium chloride and gypsum. Magnesium hydroxide destroys the structure of the cement paste; once ettringite is formed, it can cause great internal stress in the concrete, causing the concrete to expand and crack; the substitution reaction of magnesium silicate hydrate on calcium silicate hydrate reduces the strength of the concrete and makes it brittle; calcium chloride and gypsum are soluble in water, resulting in increased leaching of the concrete, followed by loss of strength and quality.

[0006] In order to prevent seawater from corroding concrete and then steel bars, the usual operating methods are to apply anti-corrosion coatings on the concrete surface to prevent corrosion; apply an anti-corrosion layer on the surface of the steel bars to slow down the corrosion of the steel bars; and use electrochemical methods for anti-corrosion.

[0007] However, the above three methods of anti-corrosion can only slow down the corrosion of concrete and internal steel bars from the surface. Once the external anti-corrosion layer is damaged, the erosion rate will be accelerated, and anti-corrosion cannot be carried out fundamentally.

[0008] Therefore, those skilled in the art provide a marine geopolymer concrete resistant to steel bar corrosion and a preparation method thereof to solve the problems raised in the above-mentioned background technology. Summary of the invention

[0009] 1. Technical issues to be resolved

[0010] In view of the shortcomings of the prior art, the present invention provides a marine geopolymer concrete that is resistant to steel bar corrosion and a preparation method, which solves the problem that conventional anti-corrosion methods can only slow down the corrosion of concrete and internal steel bars from the surface. Once the external anti-corrosion layer is destroyed, the erosion rate will be accelerated, and anti-corrosion cannot be carried out fundamentally.

[0011] (II) Technical solution

[0012] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0013] A marine geopolymer concrete resistant to steel bar corrosion comprises the following components in percentage by mass: 15%-25% of coarse aggregate, 10%-15% of fine aggregate, 5%-10% of gel material, 10%-20% of calcium nitrite, 3%-5% of sodium carbonate, 3%-5% of sodium sulfate, 0.6%-1.0% of alcoholamine compound, 5%-10% of zeolite molecular sieve, 3%-5% of nano-scale silicon dioxide powder, 1%-5% of admixture and the balance of water.

[0014] Preferably, the concrete comprises the following components in percentage by mass: 18% coarse aggregate, 13% fine aggregate, 8% gel material, 15% calcium nitrite, 4% sodium carbonate, 4% sodium sulfate, 0.8% alcoholamine compound, 8% zeolite molecular sieve, 4% nano-silica powder, 3% admixture and the balance water.

[0015] Preferably, the concrete comprises the following components in percentage by mass: 15% coarse aggregate, 10% fine aggregate, 5% gel material, 10% calcium nitrite, 3% sodium carbonate, 3% sodium sulfate, 0.6% alcoholamine compound, 5% zeolite molecular sieve, 3% nano-silica powder, 1% admixture and the balance water.

[0016] Preferably, the concrete comprises the following components in percentage by mass: 22% coarse aggregate, 15% fine aggregate, 10% gel material, 20% calcium nitrite, 5% sodium carbonate, 5% sodium sulfate, 1.0% alcoholamine compound, 10% zeolite molecular sieve, 5% nano-silica powder, 5% admixture and the balance water.

[0017] Preferably, the coarse aggregate includes mineral powder, standard sand, coarse aggregate, alkali activator and calcined hydrotalcite, and the mass ratio of the mineral powder, standard sand, coarse aggregate, alkali activator and calcined hydrotalcite is 1:(1-2):2:(1-2):(2-3). The chemical formula of the calcined hydrotalcite is MgO·aAl2O3·bH2O, wherein a is selected from any number of 0.1-0.5, and b is selected from any integer.

[0018] Preferably, the fine aggregate has a saturated surface dry apparent density of 2600 g / cm, an apparent density of 2680 g / cm, a stone powder content of 16.5%, a saturated surface dry water absorption of 3.5%, a fineness modulus of 2.5, a mud content of 0%, an organic matter content of 0%, a sulfide and sulfate content of 0.18%, and a firmness of 1.4.

[0019] Preferably, the gel material is made of siliceous and alumina raw materials such as fly ash, slag, kaolin and alkali activator, and the alcoholamine compound is a mixture of triethanolamine, triisopropanolamine and ethylene glycol monoisopropanolamine in a mass ratio of 1:(1-2):1, preferably, the mass ratio of triethanolamine, triisopropanolamine and ethylene glycol monoisopropanolamine is 1:1.5:1.

[0020] Preferably, the molar ratio of SiO2 / Al2O3 in the zeolite molecular sieve is 25-30, preferably the molar ratio of SiO2 / Al2O3 is 28.

[0021] Preferably, the admixture includes a water reducer and a steel bar rust inhibitor, and the mass ratio thereof is water reducer: steel bar rust inhibitor = 1:(1-2), preferably water reducer: steel bar rust inhibitor = 1:1.5.

[0022] Preferably, a method for preparing marine geopolymer concrete resistant to steel bar corrosion comprises the following steps:

[0023] Step S1. Weigh each raw material according to the percentage content of the raw material components for standby use;

[0024] Step S2. Put the coarse aggregate, calcium nitrite, sodium carbonate and sodium sulfate into a mixer and mix them to obtain a mixture I;

[0025] Step S3. Put the alcoholamine compound, zeolite molecular sieve, and nano-scale silica powder into a mixer, and add a certain amount of water to stir and mix to obtain a mixture II;

[0026] Step S4. Mix the mixture I and mixture II obtained above with the admixture and stir, then add the remaining amount of water and mix them thoroughly to obtain the marine geopolymer concrete.

[0027] Preferably, the mixing conditions in steps S1 and S2 are: carried out under stirring conditions, and the stirring speed is 150-300 rpm, the time is 2-5 min, and the temperature is 25-35°C; the mixing conditions in step S3 are: carried out under stirring conditions, and the stirring speed is 300-400 rpm, the time is 6-8 min, and the temperature is 30-40°C.

[0028] (III) Beneficial effects

[0029] The present invention provides a marine geopolymer concrete resistant to steel bar corrosion and a preparation method thereof. It has the following beneficial effects:

[0030] 1. The present invention provides a marine geopolymer concrete and a preparation method thereof that resists steel bar corrosion. By adding coarse aggregate to the raw materials, the calcined hydrotalcite has a small particle size and a large specific surface area. As a seed, it can accelerate the hydration process at an early stage, thereby producing more hydration products and a denser structure. At the same time, it can be filled in the pores of the matrix to improve the pore structure, the slurry-aggregate interface, etc., to prevent chloride ions and CO2 from entering the matrix, and to improve the durability of the marine geopolymer and its concrete.

[0031] 2. The present invention provides a marine geopolymer concrete resistant to steel bar corrosion and a preparation method. By adding an admixture to the raw materials, the admixture consists of a water reducer and a steel bar rust inhibitor, which can protect the steel bars inside the concrete from chloride ion corrosion, and can effectively adsorb and solidify free chloride ions, thereby ensuring the safety and durability of the marine reinforced concrete structure. The durability of the concrete is improved through the synergistic effect of multiple pathways. The water-soluble chloride ion content in the marine geopolymer concrete gradually decreases within 7 days, 28 days to 90 days, and is long-term stable after 90 days, thereby ensuring the safety and durability of the marine reinforced concrete structure and having a better anti-steel corrosion effect. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1:

[0034] An embodiment of the present invention provides a marine geopolymer concrete that is resistant to steel bar corrosion. The concrete includes the following components in percentage by mass: 18% coarse aggregate, 13% fine aggregate, 8% gel material, 15% calcium nitrite, 4% sodium carbonate, 4% sodium sulfate, 0.8% alcoholamine compound, 8% zeolite molecular sieve, 4% nano-silica powder, 3% admixture and the balance water.

[0035] The coarse aggregate includes mineral powder, standard sand, coarse aggregate, alkali activator and calcined hydrotalcite, wherein the mass ratio of the mineral powder, standard sand, coarse aggregate, alkali activator and calcined hydrotalcite is 1:2:2:1:3, and the chemical formula of the calcined hydrotalcite is MgO·aAl2O3·bH2O, wherein a is selected from any number of 0.1-0.5, and b is selected from any integer.

[0036] The alcoholamine compound is a mixture of triethanolamine, triisopropanolamine and ethylene glycol monoisopropanolamine in a mass ratio of 1:1.5:1. The molar ratio of SiO2 / Al2O3 in the zeolite molecular sieve is 28. The admixtures include a water reducer and a steel bar rust inhibitor, and the mass ratio of the water reducer: steel bar rust inhibitor is 1:1.5.

[0037] The method for preparing the marine geopolymer concrete resistant to steel bar corrosion comprises the following steps:

[0038] Step S1. Weigh each raw material according to the percentage content of the raw material components for standby use;

[0039] Step S2. Put the coarse aggregate, calcium nitrite, sodium carbonate and sodium sulfate into a mixer and mix them to obtain a mixture I;

[0040] Step S3. Put the alcoholamine compound, zeolite molecular sieve, and nano-scale silica powder into a mixer, and add a certain amount of water to stir and mix to obtain a mixture II;

[0041] Step S4. Mix the mixture I and mixture II obtained above with the admixture and stir, then add the remaining amount of water and mix them thoroughly to obtain the marine geopolymer concrete.

[0042] The mixing conditions in steps S1 and S2 are as follows: stirring at a speed of 200 rpm, for 4 min, and at a temperature of 30°C; the mixing conditions in step S3 are as follows: stirring at a speed of 350 rpm, for 7 min, and at a temperature of 35°C.

[0043] Embodiment 2:

[0044] An embodiment of the present invention provides a marine geopolymer concrete that is resistant to steel bar corrosion. The concrete includes the following components in percentage by mass: 15% coarse aggregate, 10% fine aggregate, 5% gel material, 10% calcium nitrite, 3% sodium carbonate, 3% sodium sulfate, 0.6% alcoholamine compound, 5% zeolite molecular sieve, 3% nano-silica powder, 1% admixture and the balance water.

[0045] The method for preparing the marine geopolymer concrete resistant to steel bar corrosion comprises the following steps:

[0046] Step S1. Weigh each raw material according to the percentage content of the raw material components for standby use;

[0047] Step S2. Put the coarse aggregate, calcium nitrite, sodium carbonate and sodium sulfate into a mixer and mix them to obtain a mixture I;

[0048] Step S3. Put the alcoholamine compound, zeolite molecular sieve, and nano-scale silica powder into a mixer, and add a certain amount of water to stir and mix to obtain a mixture II;

[0049] Step S4. Mix the mixture I and mixture II obtained above with the admixture and stir, then add the remaining amount of water and mix them thoroughly to obtain the marine geopolymer concrete.

[0050] The mixing conditions in steps S1 and S2 are as follows: stirring at a speed of 200 rpm, for 4 min, and at a temperature of 30°C; the mixing conditions in step S3 are as follows: stirring at a speed of 350 rpm, for 7 min, and at a temperature of 35°C.

[0051] Embodiment 3:

[0052] The embodiment of the present invention provides a marine geopolymer concrete with resistance to steel bar corrosion, which comprises the following components in percentage by mass: 22% of coarse aggregate, 15% of fine aggregate, 10% of gel material, 20% of calcium nitrite, 5% of sodium carbonate, 5% of sodium sulfate, 1.0% of alcoholamine compound, 10% of zeolite molecular sieve, 5% of nano-silicon dioxide powder, 5% of admixture and the balance of water.

[0053] The method for preparing the marine geopolymer concrete resistant to steel bar corrosion comprises the following steps:

[0054] Step S1. Weigh each raw material according to the percentage content of the raw material components for standby use;

[0055] Step S2. Put the coarse aggregate, calcium nitrite, sodium carbonate and sodium sulfate into a mixer and mix them to obtain a mixture I;

[0056] Step S3. Put the alcoholamine compound, zeolite molecular sieve, and nano-scale silica powder into a mixer, and add a certain amount of water to stir and mix to obtain a mixture II;

[0057] Step S4. Mix the mixture I and mixture II obtained above with the admixture and stir, then add the remaining amount of water and mix them thoroughly to obtain the marine geopolymer concrete.

[0058] The mixing conditions in steps S1 and S2 are as follows: stirring at a speed of 200 rpm, for 4 min, and at a temperature of 30°C; the mixing conditions in step S3 are as follows: stirring at a speed of 350 rpm, for 7 min, and at a temperature of 35°C.

[0059] Comparative Example 1:

[0060] An embodiment of the present invention provides a marine geopolymer concrete that is resistant to steel bar corrosion. The concrete includes the following components in percentage by mass: 10% coarse aggregate, 8% fine aggregate, 3% gel material, 8% calcium nitrite, 2% sodium carbonate, 2% sodium sulfate, 0.4% alcoholamine compound, 3% zeolite molecular sieve, 2% nano-silica powder, 0.5% admixture and the balance water.

[0061] The method for preparing the marine geopolymer concrete resistant to steel bar corrosion comprises the following steps:

[0062] Step S1. Weigh each raw material according to the percentage content of the raw material components for standby use;

[0063] Step S2. Put the coarse aggregate, calcium nitrite, sodium carbonate and sodium sulfate into a mixer and mix them to obtain a mixture I;

[0064] Step S3. Put the alcoholamine compound, zeolite molecular sieve, and nano-scale silica powder into a mixer, and add a certain amount of water to stir and mix to obtain a mixture II;

[0065] Step S4. Mix the mixture I and mixture II obtained above with the admixture and stir, then add the remaining amount of water and mix them thoroughly to obtain the marine geopolymer concrete.

[0066] The mixing conditions in steps S1 and S2 are as follows: stirring at a speed of 200 rpm, for 4 min, and at a temperature of 30°C; the mixing conditions in step S3 are as follows: stirring at a speed of 350 rpm, for 7 min, and at a temperature of 35°C.

[0067] Comparative Example 2:

[0068] The embodiment of the present invention provides a marine geopolymer concrete with resistance to steel bar corrosion, which comprises the following components in percentage by mass: 10% coarse aggregate, 8% fine aggregate, 12% gel material, 22% calcium nitrite, 8% sodium carbonate, 8% sodium sulfate, 2.0% alcoholamine compound, 12% zeolite molecular sieve, 8% nano-silica powder, 8% admixture and the balance water.

[0069] The method for preparing the marine geopolymer concrete resistant to steel bar corrosion comprises the following steps:

[0070] Step S1. Weigh each raw material according to the percentage content of the raw material components for standby use;

[0071] Step S2. Put the coarse aggregate, calcium nitrite, sodium carbonate and sodium sulfate into a mixer and mix them to obtain a mixture I;

[0072] Step S3. Put the alcoholamine compound, zeolite molecular sieve, and nano-scale silica powder into a mixer, and add a certain amount of water to stir and mix to obtain a mixture II;

[0073] Step S4. Mix the mixture I and mixture II obtained above with the admixture and stir, then add the remaining amount of water and mix them thoroughly to obtain the marine geopolymer concrete.

[0074] The mixing conditions in steps S1 and S2 are as follows: stirring at a speed of 200 rpm, for 4 min, and at a temperature of 30°C; the mixing conditions in step S3 are as follows: stirring at a speed of 350 rpm, for 7 min, and at a temperature of 35°C.

[0075] Experimental verification:

[0076] The marine geopolymer concrete prepared in the above Examples 1-3 and Comparative Examples 1-2 was subjected to working performance tests and mechanical performance tests. The working performance test included slump, slump spread test, and concrete density test, and the test was conducted in accordance with the "Testing Procedure for Cement and Cement Concrete" (JTG_E30-2005); the mechanical performance test included a compressive strength test, and the test was conducted in accordance with the "Test Method for Mechanical Properties of Ordinary Concrete" (GB / T50081-2002). The experimental results are shown in Table 1 below:

[0077] Table 1 Results of working performance test and mechanical properties test of marine polymer concrete

[0078]

[0079]

[0080] It can be concluded from the experimental results in Table 1 above that the slump, slump spread, density and compressive strength of the embodiments of the present invention are all in compliance with the standard requirements, are better than the comparative examples, and the comprehensive performance embodiment 1 is the best.

[0081] The marine geopolymer concrete prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-2 was subjected to a durability test. The durability test was mainly for the diffusion coefficient. The diffusion coefficient test was carried out in accordance with the relevant provisions of the "Test Method for Long-term Performance and Durability of Ordinary Concrete" (GBJ82-85) (RCM method). The durability values ​​at 28 days, 56 days and 90 days were measured. The experimental results are shown in Table 2 below:

[0082] Table 2 Durability test results of marine polymer concrete

[0083] <![CDATA[28 days (unit / 10 -12 m 2 / s)]]> <![CDATA[56 days (unit / 10 -12 m 2 / s)]]> <![CDATA[90 days (unit / 10 -12 m 2 / s)]]> Example 1 1.852 1.723 1.225 Example 2 1.998 1.782 1.356 Example 3 1.898 1.856 1.372 Comparative Example 1 2.368 2.152 1.697 Comparative Example 2 2.456 2.098 1.586

[0084] From the experimental results in Table 2 above, it can be concluded that the marine engineering concrete of the present invention has strong durability, and the diffusion degree after 90 days is less than 1.5×10 -12 m 2 / s.

[0085] It can be seen from the above experimental results that the marine engineering concrete of the embodiment of the present invention has strong durability and anti-corrosion performance.

[0086] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A marine geopolymer concrete resistant to steel bar corrosion, characterized in that: The concrete comprises the following components in percentage by mass: 15%-25% of coarse aggregate, 10%-15% of fine aggregate, 5%-10% of gel material, 10%-20% of calcium nitrite, 3%-5% of sodium carbonate, 3%-5% of sodium sulfate, 0.6%-1.0% of alcoholamine compound, 5%-10% of zeolite molecular sieve, 3%-5% of nano-scale silicon dioxide powder, 1%-5% of admixture and the balance of water.

2. The marine geopolymer concrete for resisting steel bar corrosion according to claim 1, characterized in that: The concrete comprises the following components in percentage by mass: 18% of coarse aggregate, 13% of fine aggregate, 8% of gel material, 15% of calcium nitrite, 4% of sodium carbonate, 4% of sodium sulfate, 0.8% of alcoholamine compound, 8% of zeolite molecular sieve, 4% of nano-scale silicon dioxide powder, 3% of admixture and the balance of water.

3. The marine geopolymer concrete for resisting steel bar corrosion according to claim 1, characterized in that: The concrete comprises the following components in percentage by mass: 15% of coarse aggregate, 10% of fine aggregate, 5% of gel material, 10% of calcium nitrite, 3% of sodium carbonate, 3% of sodium sulfate, 0.6% of alcoholamine compound, 5% of zeolite molecular sieve, 3% of nano-scale silicon dioxide powder, 1% of admixture and the balance of water.

4. The marine geopolymer concrete for resisting steel bar corrosion according to claim 1, characterized in that: The concrete comprises the following components in percentage by mass: 22% of coarse aggregate, 15% of fine aggregate, 10% of gel material, 20% of calcium nitrite, 5% of sodium carbonate, 5% of sodium sulfate, 1.0% of alcoholamine compound, 10% of zeolite molecular sieve, 5% of nano-scale silicon dioxide powder, 5% of admixture and the balance of water.

5. The marine geopolymer concrete for resisting steel bar corrosion according to claim 1, characterized in that: The coarse aggregate includes mineral powder, standard sand, coarse aggregate, alkali activator and calcined hydrotalcite. The mass ratio of the mineral powder, standard sand, coarse aggregate, alkali activator and calcined hydrotalcite is 1:(1-2):2:(1-2):(2-3). The chemical formula of the calcined hydrotalcite is MgO·aAl2O3·bH2O, wherein a is selected from any number between 0.1 and 0.5, and b is selected from any integer.

6. The marine geopolymer concrete for resisting steel bar corrosion according to claim 1, characterized in that: The gel material is made of siliceous and alumina raw materials such as fly ash, slag, kaolin and alkali activator. The alcoholamine compound is a mixture of triethanolamine, triisopropanolamine and ethylene glycol monoisopropanolamine in a mass ratio of 1:(1-2):1, preferably a mixture of triethanolamine, triisopropanolamine and ethylene glycol monoisopropanolamine in a mass ratio of 1:1.5:

1.

7. The marine geopolymer concrete for resisting steel bar corrosion according to claim 1, characterized in that: The molar ratio of SiO2 / Al2O3 in the zeolite molecular sieve is 25-30, preferably the molar ratio of SiO2 / Al2O3 is 28.

8. The marine geopolymer concrete for resisting steel bar corrosion according to claim 1, characterized in that: The admixture includes a water reducer and a steel bar rust inhibitor, and the mass ratio thereof is water reducer: steel bar rust inhibitor = 1: (1-2), preferably water reducer: steel bar rust inhibitor = 1: 1.

5.

9. A method for preparing marine geopolymer concrete resistant to steel bar corrosion, characterized in that: The following steps are involved: Step S1. Weigh each raw material according to the percentage content of the raw material components for standby use; Step S2. Put the coarse aggregate, calcium nitrite, sodium carbonate and sodium sulfate into a mixer and mix them to obtain a mixture I; Step S3. Put the alcoholamine compound, zeolite molecular sieve, and nano-scale silica powder into a mixer, and add a certain amount of water to stir and mix to obtain a mixture II; Step S4. Mix the mixture I and mixture II obtained above with the admixture and stir, then add the remaining amount of water and mix them thoroughly to obtain the marine geopolymer concrete.

10. The method for preparing a marine geopolymer concrete resistant to steel bar corrosion according to claim 9, characterized in that: The mixing conditions in steps S1 and S2 are: carried out under stirring conditions, and the stirring speed is 150-300 rpm, the time is 2-5 min, and the temperature is 25-35°C. The mixing conditions in step S3 are: carried out under stirring conditions, and the stirring speed is 300-400 rpm, the time is 6-8 min, and the temperature is 30-40°C.

Citation Information

Patent Citations

  • Marine concrete

    CN103936373A

  • Seawater and sea sand-based anticorrosive additive for producing marine high-performance concrete

    CN106277907A

  • Calcined hydrotalcite and preparation method thereof, composition for preparing high-durability marine concrete, concrete and preparation method thereof

    CN115924945A

Cited By

  • A curing method for improving the reinforcement protection performance of alkali-activated slag cementitious materials

    CN122749002A